[14C]‐AZD1152 drug substance manufacture: challenges of an IV‐infusion dosed human mass balance study in patients. (12th May 2016) - Bushby, Nick; Bergin, Julie; Harding, John
Abstract : [ 14 C]‐AZD1152 (barasertib) drug substance was prepared in order to support a hADME study that was to be dosed as an intravenous infusion to patients with acute myeloid leukaemia. A long patient recruitment time (1–2 years) was expected, and because of its limited stability several batches of [ 14 C]‐AZD1152 drug substance needed to be prepared in order to maintain a supply of [ 14 C]‐AZD1152 in the clinic over this period. A method was developed to purify the [ 14 C]‐AZD1152 to a GMP‐like standard at high specific activity to provide material for each of these batches. This approach to the delivery of the drug substance was successful in supplying the study with radiolabelled drug for over 1 year until all patients had been recruited. Abstract : [ 14 C]AZD1152 (barasertib) drug substance was prepared in order to support a hADME study that was to be dosed as an intravenous (IV) infusion to acute myeloid leukemia (AML) patients. A method was developed to purify the [ 14 C]AZD1152 to a GMP‐like standard at high specific activity to provide several batches of the [ 14 C]AZD1152 drug substance.